1989
DOI: 10.1190/1.1442737
|View full text |Cite
|
Sign up to set email alerts
|

Porosity identification using amplitude variations with offset: Examples from South Sumatra

Abstract: Widespread deposition of platform and reefal carbonates of the Baturaja limestone formation occurred during the Miocene epoch in the South Sumatra basin. Although significant oil and gas deposits have been discovered in the porous facies, porosity within the Baturaja limestone has been observed to vary widely between tight platform facies and highly porous reefal facies, making predrill prediction of porosity an important exploration objective. I use amplitude‐versus‐offset seismic modeling to distinguish betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Rock‐physics modelling indicates that post‐stack and amplitude‐versus‐angle (AVA) behaviour for a given lithology are controlled by porosity and the presence of hydrocarbons (Castagna, Batzle and Kan 1993). AVA analysis has traditionally been applied to clastic environments but has, within the last decade, been used as a successful porosity predictor in carbonates (Chacko 1989; Landrø, Buland and D'Angelo1995; Santoso et al 1995; D'Angelo, Brandal and Rørvik 1997; Li and Downton 2000). However, AVA analysis as a fluid prediction tool in carbonates has only been applied successfully in a limited number of cases (Megson 1992; Chiburis 1993; Adriansyah and McMechan 2001; Japsen et al 2004) and unique hydrocarbon signatures are only found in extraordinary conditions of very high porosity and gas saturation because the hydrocarbon effect is believed to overlap the changes caused by variations in porosity (Megson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Rock‐physics modelling indicates that post‐stack and amplitude‐versus‐angle (AVA) behaviour for a given lithology are controlled by porosity and the presence of hydrocarbons (Castagna, Batzle and Kan 1993). AVA analysis has traditionally been applied to clastic environments but has, within the last decade, been used as a successful porosity predictor in carbonates (Chacko 1989; Landrø, Buland and D'Angelo1995; Santoso et al 1995; D'Angelo, Brandal and Rørvik 1997; Li and Downton 2000). However, AVA analysis as a fluid prediction tool in carbonates has only been applied successfully in a limited number of cases (Megson 1992; Chiburis 1993; Adriansyah and McMechan 2001; Japsen et al 2004) and unique hydrocarbon signatures are only found in extraordinary conditions of very high porosity and gas saturation because the hydrocarbon effect is believed to overlap the changes caused by variations in porosity (Megson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For some time, single angle stack inversion was regarded as sufficient for carbonates due to the expectation that there was little AVO associated with carbonates. The basis of this is the supposed and reported invariance of the V P ∕V S with respect to changes in porosity (e.g., Chako, 1989) and the insensitivity with respect to pore fluids (e.g., Rafavich et al, 1984). Recently, there have been 1 Ikon Science, Kuala Lumpur, Malaysia.…”
Section: Introductionmentioning
confidence: 95%
“…In the case of carbonate sulfur deposits, seismic interpretation is mainly focused on porosity changes at the top of the layer and within the carbonate interval. An increase in porosity results in a drop of the amplitude in the wave reflected from the top of the carbonate sediments, which in some cases may result in a dim spot or even a phase reversal (e.g., [9]). To seismically detect the sulfur ore we should investigate relationships between the amplitude of the reflected wave and porosity, as well as the percentage of sulfur within the cap rock.…”
Section: Introductionmentioning
confidence: 99%